Pengaruh Pemberian JusTomat (Solanium Lycopersicum) Pada Lansia Penderita Hipertensi - Estiyani, Arum; Yulaeka, Yulaeka; Utami, Siswi (Jurnal Ilmu Kebidanan, 2025)
Background: Exclusive breastfeeding optimizes the physical, mental, and emotional development of infants. Exclusive breastfeeding during infancy has been shown to have long-term effects, such as a reduced risk of obesity, diabetes, and heart disease in adulthood (Indonesian Ministry of Health, 2021). Several factors influence exclusive breastfeeding, one of which is husband support. Mothers need support from those around them to support the success of exclusive breastfeeding, especially from their husbands. Methods: This study used a correlational analytic method with a cross sectional approach. Result: The results showed that of the 42 respondents, most had husband support in the high support category, namely 30 respondents (71.4%), most had family support in the high support category, namely 24 respondents (57.1%), and most gave exclusive breastfeeding to their babies, namely 31 respondents (73.8%). The results of statistical analysis with Spearman's test obtained a significant degree value ρ (0.000) < α (0.05) and r 0.963. Conclusion: There is an effect of husband's support on the success of exclusive breastfeeding at Kasiman Health Center in 2024. It is expected that breastfeeding mothers are able to implement the breastfeeding program only for 6 months then the mother can provide complementary foods after the baby is 6 months old. Breastfeeding mothers can counteract existing traditions not to follow the recommendations of others to provide complementary foods early.